The Code of Ur-Namma and the sìla Measure - Zaccagnini, Carlo (Orientalia, 2024)
This note offers a fresh interpretation of the sìla (measurement of capacity and weight) mentioned in the Prologue of Ur-Namma’s Law Code by comparing the Sippar manuscript (Si 277: I 11-21) with the the Nippur manuscript (Ni 3191: IV 1-10).